Weeding of library collections in selected private high school libraries in Quezon City - Galang, Arnor T. (1999)
The general purpose of this study is to determine the status of weeding of library collections in twenty-five selected private high school libraries in Quezon City. The survey method was used in the study. The study: 1)determined if weeding the library collection is an integral part of the collection management programs of private high school libraries in Quezon City; 2) determined if their written collection development policies include statements on the weeding of library collection; 3) identified their reasons in weeding out their library collections; 4) determined the methods and criteria in weeding; and 5) presented the problems encountered by these libraries in weeding library collections and came up with recommendations deemed useful for other high school libraries.